PEMBERDAYAAN KADER POSYANDU DALAM DETEKSI DINI KEHAMILAN RISIKO TINGGI DENGAN SKRINING KARTU SKOR POEDJI ROCHJATI DI WILAYAH KERJA PUSKESMAS SATELIT KOTA BANDAR LAMPUNG - Yanti, Fitri; Milindasari, Praty (Akademi Keperawatan Bunda Delima, 2023)
The maternal mortality rate (MMR) during pregnancy is still quite high, estimated at 115 per 100,000 live births by 2020. The cause of the high maternal mortality rate may be due to inadequate quality of health care services for pregnant women and childbirth, poor health status of pregnant women such as anemia. , pregnant women with diabetes, hypertension, tuberculosis, HIV, hepatitis B. and four more. One of the efforts to reduce maternal mortality (MMR) is to increase the use of community health facilities, starting with antenatal care by recognizing the presence of pregnant women at risk. high chance through screening or early detection, one of which can be done by posyandu officer. The purpose of this service is to increase managers' knowledge about early detection of high-risk pregnancies using the Poedji Rochjati Scorecard Screening. This service approach includes counseling for early detection of high-risk pregnancies. The results of this activity show that, the average test score before the submission of documents is 75, while after the submission of documents and training, the average value increases to 86. Based on the results of the table, the value of knowledge has increased to 16%. Keyword : MMR, Early detection, Cadre